Bottom-up C60 fullerene construction from a fluorinated C 60H21F9 precursor by laser-induced tandem cyclization - Kabdulov, Mikhail; Jansen, Martin; Amsharov, Konstantin (Chemistry - A European Journal, 2013)
Wrap up: A specially fluorinated C60 fullerene precursor (see figure) was converted to the target C60 cage by laser ionization, resulting in highly selective HF elimination without any detectable side reactions or undesired fragmentation. The fully selective transformation to the target fullerene has been unambiguously demonstrated from a 13C- labeled precursor. In general the findings open new horizons for the synthesis of carbon-based nanomaterials, which cannot be obtained by any conventional alternative method. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: arenes; fullerenes; mass spectrometry; rational synthesis